2023
DOI: 10.1111/dom.14980
|View full text |Cite
|
Sign up to set email alerts
|

The role of dietary salt in metabolism and energy balance: Insights beyond cardiovascular disease

Abstract: Dietary salt (NaCl) is essential to an organism's survival. However, today's diets are dominated by excessive salt intake, which significantly impacts individual and population health. High salt intake is closely linked to cardiovascular disease (CVD), especially hypertension, through a number of well-studied mechanisms. Emerging evidence indicates that salt overconsumption may also be associated with metabolic disorders. In this review, we first summarize recent updates on the mechanisms of salt-induced CVD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 211 publications
(454 reference statements)
0
6
0
Order By: Relevance
“…Current studies provide strong evidence supporting the correlation between sodium intake and blood pressure levels; they also indicate that excessive consumption of sodium is linked to various other negative health conditions, including metabolic, gastrointestinal, and bone disorders [22][23][24][25][26]. Research suggests that a high intake of sodium can disrupt metabolism through mechanisms such as leptin resistance, overproduction of fructose and ghrelin, and insulin resistance [23].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Current studies provide strong evidence supporting the correlation between sodium intake and blood pressure levels; they also indicate that excessive consumption of sodium is linked to various other negative health conditions, including metabolic, gastrointestinal, and bone disorders [22][23][24][25][26]. Research suggests that a high intake of sodium can disrupt metabolism through mechanisms such as leptin resistance, overproduction of fructose and ghrelin, and insulin resistance [23].…”
Section: Introductionmentioning
confidence: 91%
“…Current studies provide strong evidence supporting the correlation between sodium intake and blood pressure levels; they also indicate that excessive consumption of sodium is linked to various other negative health conditions, including metabolic, gastrointestinal, and bone disorders [ 22 , 23 , 24 , 25 , 26 ]. Research suggests that a high intake of sodium can disrupt metabolism through mechanisms such as leptin resistance, overproduction of fructose and ghrelin, and insulin resistance [ 23 ]. In a cohort study conducted by Takase et al [ 24 , 25 ], it was observed that increased salt intake correlated with a higher number of metabolic disorders and an elevated risk of developing metabolic syndrome.…”
Section: Introductionmentioning
confidence: 96%
“…In the last 20 years, attention has increasingly been paid to the role of innate immune cells and their proinflammatory responses in salt-sensitive hypertension. 51,52 As previously reviewed, 53,54 innate and adaptive immunometabolism has been found to be impacted by sodium intake. Immunometabolism involves understanding of how the metabolic processes within immune cells influence their function and how immune responses, in turn, impact cellular metabolism.…”
Section: Innate Immune Cells and Inflammatory Biomarkers In Salt-sens...mentioning
confidence: 99%
“…55 Various studies have linked salt intake with energy balance and regulation of other hormones. 54 Studies on immunometabolism have primarily focused on TH17 cells and T regulatory cells, which rely on the SGK1 (Serum/ Glucocorticoid Regulated Kinase 1)-FOXO1 (Forkhead box protein O1) axis, thus increasing susceptibility to autoimmune diseases. [56][57][58] Macrophage metabolism and homeostasis have also been shown to be impacted by sodium via mitochondrial-dependent pathways.…”
Section: Innate Immune Cells and Inflammatory Biomarkers In Salt-sens...mentioning
confidence: 99%
“…A higher intake of sodium may lead to other conditions beyond CVD, targeting several organ systems (e.g., the kidney, brain, bone, gastrointestinal tract, immune system, as reviewed by Vinitha et al [27]), or inducing metabolic changes that may impact the gut microbiome [28], energy balance, and obesity development (reviewed by Wu et al [29]).…”
mentioning
confidence: 99%